Exploring the Role of Distributed Learning in Distance Education at Allama Iqbal Open University: Academic Challenges at Postgraduate Level - Bukhsh, Qadir; Chaudhary, Muhammad Ajmal (Turkish Online Journal of Distance Education, 2015)
Distributed learning is derived from the concept of distributed resources. Different institutions around the globe connected through network and the learners are diverse, located in the different cultures and communities. Distributed learning provides global standards of quality to all learners through synchronous and asynchronous communications and provides the opportunity of flexible and independent learning with equity, low cost educational services and has become the first choice of the dispersed learners around the globe. The present study was undertaken to investigate the challenges faced by the Faculty Members of Department of Business Administration and Computer Science at Allama Iqbal Open University Islamabad Pakistan. 25 Faculty Members were taken as sample of the study from both Departments (100% Sampling). The study was qualitative in nature and interview was the data collection tool. Data was analyzed by thematic analysis technique. The major challenges faced by the Faculty Members were as: bandwidth, synchronous learning activities, irregularity of the learners, feedback on individual work, designing and managing the learning activities, quality issues and training to use the network for teaching learning activities.
KerkoCite.ItemAlsoKnownAs: 10.17718/tojde.00342 10/gf62h3 2129771:539U4TUB
Keywords: _C:Germany DEU; _C:India IND; _C:Pakistan PAK; _C:Turkey TUR; __C:filed:1; __C:scheme:1